The Development of Christian Care Aid in Zimbabwe: The Case of Matabeleland Region, 1967-c.1990 (Historia, 2023)
The organisation, Christian Care, was formed during Zimbabwe’s liberation war in 1967 to disburse emergency aid to victims of the war and political repression. From 1967 to about 1990, it provided emergency relief and charity aid to victims of war and the marginalised people in Zimbabwe. This article explores the development of Christian Care aid from its inception to around 1990, tracing the changes over time. It shows how Christian Care managed to respond to the situation on the ground even when such an agenda was not in line with what the government of the day practised. Between 1967 and 1980, Christian Care’s aid was largely emergency based, assisting war victims with food, clothes and money. After 1980, the nature and composition of aid changed to development projects such as drilling of boreholes, construction of schools, clinics and dams and assisting communities to set up income generating projects like market gardens. Using a qualitative research methodology with predominantly archival sources, I explore the development of Christian Care aid in the Matabeleland region of Zimbabwe, demonstrating how the organisation provided assistance to the repressed and marginalised.
Keywords: Christian Care; Zimbabwe; Matabeleland; emergency aid; governance; community development